Effect of portal-systemic anastomosis on renal haemodynamics in cirrhosis. Issue 11 (November 1976) - Ring-Larsen, H; Hesse, B; Stigsby, B
Abstract : In 12 patients with portal hypertension and repeated bleedings from oesophageal varices the central haemodynamics, portal pressure, and mean renal blood flow (RBF) were investigated immediately before and two to seven months after portal-systemic shunt. Cardiac output increased significantly, whereas arterial pressure was unchanged after operation. RBF, which was initially less than in controls, did not change. As portal pressure decreased significantly, a direct portal-renal, neural, or humoral reflex mechanism does not explain the subnormal RBF in cirrhosis. As plasma volume was large and unchanged after operation a "diminished circulating plasma volume" is an unlikely explanation. Therefore, on the basis of the present observations, previously postulated causes of renal hypoperfusion in cirrhosis need revision.